Leucaena hedgerow intercropping and cattle manure application in the Ethiopian highlands. III. Nutrient balances - Lupwayi, N.Z.; Haque, I. (Springer, 1998)
Balances between nutrients applied or mineralized and nutrients removed in maize grain and stover were calculated in a hedgerow intercropping experiment in which Leucaena leucocephala and L. pallida prunings and cattle manure were applied. Hedgerow intercropping (also called alley cropping) is an agroforestry system in which trees are grown in dense hedges between alleys where short-cycle crops are grown. The hedges are pruned periodically during the cropping period and the prunings are added to the soil as green manure. In control treatments, nutrient depletion per season was in the order of 7-19 kg N ha-1, 4-12 kg P ha-1, 10-26 kg K ha-1, 0-2 kg Ca ha-1 and 3-6 kg Mg ha-1, N fertilizer reversed the depletion of N, but it accelerated the depletion of the other nutrients. Manure and at least two application of leucaena prunings resulted in net positive balances of N. K. and Ca between amounts applied or mineralized and amounts removed by maize. The amounts of P and Mg applied with or mineralized from prunings or manure were insufficient to offset the negative balances of these nutrients.